Re-thinking the growth of London. An interactive multi-stakeholder perspective derived in geodesign and negotiation - Carl Steinitz (Area, 2022)
The Cambridge-Milton Keynes-Oxford (CAMKOX) Corridor is the fastest growing region in the United Kingdom. The UK National Infrastructure Commission proposes to add 780,000 housing units and 1,450,000 people to the existing CAMKOX population of around 3,300,000. However, it is highly likely that the conditions under which this objective would be met by 2050 will be substantially different from those of today. The direct and indirect impacts of projected climate change, demographic growth and technical innovation must be considered in relationship to current conditions. In this context, a two-day workshop was organized among interested stakeholders by the Centre for Advanced Spatial Analysis of University College London, with the participation of 20 professional planners and academics with CAMKOX experience. Geodesign modifies geography by design at intentional change. It tightly couples the creation of proposals for change with impact simulations informed by geographic contexts and systems thinking. Coming to a politically acceptable planning strategy inevitably implies negotiation among local people, aided by geographic scientists and design professionals, supported by information technologists. The digital tools to enable a collaboratively negotiated consensus are based on diagrams of policies and projects to produce an outcome only indicating that “It can be…or might be… something like this”. Participant teams each applied one of three scenarios of early, late, or non-adoption of systems policy and project innovations, reporting the designs and their impacts at three time-steps, 2020 (existing), 2035, and 2050. These were compared and negotiated to one final design.